2019
DOI: 10.3389/feduc.2019.00089
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Holistic Marks With Analytic Rubrics

Abstract: Analytic and holistic marking are typically researched as opposites, generating a mixed and inconclusive evidence base. Holistic marking is low on content validity but efficient. Analytic approaches are praised for transparency and detailed feedback. Capturing complex criteria interactions, when deciding marks, is claimed to be better suited to holistic approaches whilst analytic rules are thought to be limited. Both guidance and evidence in this area remain limited to date. Drawing from the known complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
(118 reference statements)
2
15
0
2
Order By: Relevance
“…We also found that unpacking of analytic bins can help determine if the item elicits critical components of the holistic rubric and if the item elicits all 5 levels of the LP. This is similar to a finding reported by Tomas et al (2019) that having humans apply both holistic and analytic codes helped define some of the criteria underlying the holistic scoring. We found that we were able to achieve good performing models with both ML platforms tested, although there is some evidence that CRC performed better than LightSide on some items using analytic composite scores, this was not true for all items or true for using holistic scores.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We also found that unpacking of analytic bins can help determine if the item elicits critical components of the holistic rubric and if the item elicits all 5 levels of the LP. This is similar to a finding reported by Tomas et al (2019) that having humans apply both holistic and analytic codes helped define some of the criteria underlying the holistic scoring. We found that we were able to achieve good performing models with both ML platforms tested, although there is some evidence that CRC performed better than LightSide on some items using analytic composite scores, this was not true for all items or true for using holistic scores.…”
Section: Discussionsupporting
confidence: 88%
“…However, this increase in model accuracy was not uniformly achieved across all items and took significant effort and time to achieve, mainly in rubric design and additional coding time. Harsch and Martin (2013) and Tomas et al (2019) argue that holistic and analytic approaches can be combined to offer productive outcomes for both research and practice. One possible extension of this is to investigate the combination of both holistic and analytic coding to generate one improved ML model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations